Thailand’s Sufficiency Economy Philosophy as an Alternative Path to Sustainable Development - Jitsuchon, Somchai (European Journal of Sustainable Development, 2019)
The recent history of economic and social development has shown that while contemporary development models succeed in increasing the wealth and wellbeing of mankind around the world, they also suffer from a number of shortcomings: they emphasize too much on financial success (like GDP) at the expense of other important dimensions of development, they bring in occasional but more frequent crises of various sort, they entail numerous social, such as disparity, and environmental illnesses. In short, the current development models are not sustainable. While Sustainable Development Goals (SDGs) is an attempt to achieve sustainable development by setting up goals that would steer the development in right direction, it lacks description of how those goals should be achieved. Rather, SDGs recognize that countries may have their own ways to achieve the goals. In this paper, we argue that Sufficiency Economy Philosophy (SEP), invented by the late King Bhumibol Adulyadej of Thailand, offers an alternative path to sustainable development. Key differences of SEP from other development models are that (a) it is a more holistic way of development, with physical and spiritual betterment simultaneously being sought, (b) it regards development as a multi-dimensional endeavor from the outset and, (c) it recognizes the role of communities and voluntary participation in development as important components on the path to sustainable development. We use a simple model that links SEP to sustainable development outcomes and test it with a newly-constructed system of indicators that captures SEP principles held by Thai people and a number of ultimate development outcomes. Our results find positive contributions of SEP to sustainable development outcomes. The indicators can thus be used to monitor both SEP and sustainable development. Keywords: Path to sustainable development, Development Indicators, King Bhumibol Adulyadej, Sufficiency, economy philosophy